2022
DOI: 10.1172/jci.insight.157855
|View full text |Cite
|
Sign up to set email alerts
|

HIF1A-dependent induction of alveolar epithelial PFKFB3 dampens acute lung injury

Abstract: Acute lung injury (ALI) is a severe form of lung inflammation causing acute respiratory distress syndrome in patients. ALI pathogenesis is closely linked to uncontrolled alveolar inflammation.We hypothesize that specific enzymes of the glycolytic pathway could function as key regulators of alveolar inflammation. Therefore, we screened isolated alveolar epithelia from mice exposed to ALI induced by injurious ventilation to assess their metabolic responses. These studies pointed us towards a selective role for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 72 publications
4
18
0
Order By: Relevance
“…The acid aspiration model of ALI was described previously 3,4,14,15 . Mice were anesthetized with isoflurane and suspended by their incisors at 45° angle.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The acid aspiration model of ALI was described previously 3,4,14,15 . Mice were anesthetized with isoflurane and suspended by their incisors at 45° angle.…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that the glycolytic shift of ATII cells in response to injurious stimuli protects against experimental ALI. 3 We hypothesized that the metabolic activity of the alveolar epithelium impacts the alveolar macrophage function. To study the interactions between ATII cells and macrophages, we utilized a non-contact co-culture system.…”
Section: Alveolar Epithelial Cells Dampen the Release Of Pro-inflamma...mentioning
confidence: 99%
See 2 more Smart Citations
“…For mRNA gene expression assay, cDNA was synthesized using High-Capacity cDNA Reverse Isolation murine alveolar epithelial cells. The protocol to isolate alveolar epithelial cells is adapted from previous publication 53 . For alveolar epithelial cell isolation, mice were euthanized by pentobarbital overdose.…”
Section: Declarationsmentioning
confidence: 99%